Analisis Keterampilan Mengajar Calon Guru Pendidikan Teknik Informatika dan Komputer Pada Matakuliah Microteaching - Gundo, Adriyanto Juliastomo (Peneliti.net, 2024)
SA teacher is required to have good teaching skills. The teaching skills or competencies referred to are eight teacher teaching skills. As prospective educators/teachers, students of the Informatics Engineering Education Study Program (PTIK) are required to master eight teacher teaching skills. This research aims to describe the teaching skills possessed by PTIK students in terms of: opening and closing lessons, explanation skills, skills in using variations, asking questions, reinforcement skills, small group and individual teaching skills, group discussion guiding skills, and class management skills. . The results obtained were that the teaching skills of prospective PTIK teachers were on average between 81.25 to 85.55 in the good category.